THE EFFECT OF AUDIT COMMITTEE, INSTITUTIONAL OWNERSHIP, PROFITABILTY, AND AUDIT COMPLEXITY AS MODERATING VARIABLE TO FINANCIAL STATEMENT REPORT DELAY (Empirical Study on Manufacturing Companies Listed on Indonesia Stock Exchange Year 2017-2019) - Rifqi Husein Aldjoeffry; Surya Raharja (Diponegoro Journal of Accounting, 2022)
The purpose of this study was to determine the effect of the audit committee moderated by audit complexity, institutional ownership, and profitability on financial statement report delay by conducting an empirical study on manufacturing companies listed on IDX in 2017 – 2019. This study uses quantitative methods and explanatory research that aims to prove the research hypothesis. The sample selection was carried out by purposive sampling and based on predetermined criteria; the number of samples used was 83 manufacturing companies. The data analysis technique in this study is multiple linear regression assisted by the statistics application of SPSS. The results showed that institutional ownership and profitability had a negative effect on financial statement report delay, while the audit committee had no significant effect on financial statement report delay. In addition, audit complexity does not moderate the effect of the audit committee on financial statement report delay.